2018
DOI: 10.1186/s40695-018-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disorder, exposure to violence, and perceived discrimination in relation to symptoms in midlife women

Abstract: BackgroundSome symptoms at midlife are associated with stress, such as hot flashes, trouble sleeping, headaches, or depressed mood. Hot flashes have been studied in relation to laboratory stressors, physiological biomarkers, and self-reported stress, but less is known about hot flashes in relation to the larger context of women’s lives. This study examined the risk of symptoms in relation to neighborhood disorder, exposure to neighborhood violence, social cohesion and perceived discrimination. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Their study revealed that everyday mistreatment was associated with higher allostatic load, above and beyond the independent association of lifetime discrimination. Gerber and Sievert’s (2018) study revealed that neighborhood disorder and social cohesion, as well as everyday discrimination, were associated with a number of adverse physical and mental health outcomes.…”
Section: Theory and Evidencementioning
confidence: 99%
“…Their study revealed that everyday mistreatment was associated with higher allostatic load, above and beyond the independent association of lifetime discrimination. Gerber and Sievert’s (2018) study revealed that neighborhood disorder and social cohesion, as well as everyday discrimination, were associated with a number of adverse physical and mental health outcomes.…”
Section: Theory and Evidencementioning
confidence: 99%
“…African American women face significant socioeconomic, environmental, and relational stressors. Some of these stressors include race/ethnic discrimination that can affect education, employment, and residential opportunities, neighborhood safety, higher levels of bereavement, and disproportionately lower marital relationships compared with other women (Albert, 2019; Gerber & Sievert, 2018; Lewis, Cogburn, & Williams, 2015; Williams, 2018).…”
mentioning
confidence: 99%
“…46 Gerber and colleagues 67 assessed the cross-sectional association between everyday discrimination and midlife symptoms of fatigue and hot flashes at one timepoint 52 in a sample of 139 Black and White women aged 40 to 60 years in New York City. 46 In that study, discrimination was associated with lack of energy but, in contrast to our results, not hot flashes. It may be that considering VMS (both hot flashes and night sweats) longitudinally over the course of the menopause transition better captures a woman's experience of VMS than a single measure eliciting information for one 2-week period in a woman's life.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined the association between concurrent reports of everyday discrimination and VMS over the menopause transition. Second, given that the one previous study of discrimination and VMS relied on cross-sectional data 46 and the potential for chronic discrimination (discrimination reported at multiple time points) to be more strongly related to health compared with discrimination reported once, 24,47-49 we examined a potential temporal association between chronic discrimination reported at the first four visits and longitudinal trajectories of VMS over the menopausal transition. Finally, we evaluated whether the disproportionate burden of VMS in Black women persisted after accounting for discrimination in midlife and other known risk factors for VMS.…”
mentioning
confidence: 99%